Evaluation of Yield and Productivity of 20 Single-Cross Maize Hybrid Combinations - Hidayatullah, Taufiq; Suliansyah, Irfan; Swasti, Etti; Putri, Nurwanita Ekasari; Mejaya, I Made Jana (Jurnal Biologi Tropis, 2025)
Maize is a leading commodity in the agricultural industry. Efforts to increase maize seed production and quality are very important, considering the important role of maize commodities in the global and local food systems. This study aims to evaluate the production results of 20 single-cross maize hybrid combinations through the analysis of agronomic traits and productivity results. The experiment was conducted using a randomized block design with three replications in 60  plots. The agronomic characters observed included cob length, cob diameter, number of seed rows per cob, and seed weight per cob. The Genotype R hybrid combination stands out as a superior variety with the highest productivity, supported by strong agronomic characteristics. Meanwhile, the Genotype T hybrid shows the lowest performance, highlighting the importance of developing varieties suited to specific environmental conditions. This research makes a significant contribution to agricultural innovation in Indonesia, especially in improving food security and productivity of the agricultural sector.